A Cycloaddition Strategy for Use toward Berkelic Acid, an MMP Inhibitor and Potent Anticancer Agent Displaying a Unique Chroman Spiroketal Motif - Huang, Yaodong (2008)
A kinetically controlled diastereoselective cycloaddition between a chiral enol ether and an ortho-quinone methide (o-QM) produces a chroman spiroketal motif that is found in the core of berkelic acid, a novel matrix metalloproteinase (MMP) inhibitor and potent anticancer agent. The transformation lays the groundwork for preparation of future inhibitors aimed at distinguishing among the active sites of the twenty-three known MMP. Experimental findings suggest that the stereochemistry that emerges from cycloaddition is opposite that which results from thermodynamic ketalization.